Free Trade Zone Sebagai Salah Satu Wujud Implementasi Konsep Disentralisasi - Kurniawan, Wishnu (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2017)
Indonesia is a country that adopts welfarestate system where the state administration is aiming for the prosperous of society. The excistense of statehood based on Pancasila ideology and constituion of 1945 with desentralization principal government system. Desentralization system are system wich the authorize to manage and developed by the regional government/local government. That system excepting as otherwise stipulated in legislation. Distribution authority to region/local government is a manifestation of the spirit of the countrys development based on Region/Local Authonomy. Fulfillment of prosperous for society, central government of Negara Kesatuan Republik Indonesia forming an area exclusively dedicated to the development and investment strategies in increasing state revenues. In order to increase fulfillment the prosperous, needed an authority who focus on build and developed the special region to face the infrastructure developed in order to developed direct investment. This system made the Central Government intervened the Local/Region Government. The intervened reflected by Lawa Number 44 of 2007 juncto Governement Regulation Number 46 of 2007 about Free Trade and Free Port of Batam Island. The principal of implementing Free Trade Zone in Batam Island with special authority as executor contained inrelated with Desentralization principal. That system in accordance with Indonesian Constituion of 1945 specially in article 18B paragraph (1) wich specifies that the state respected with the special unit â a unit areas and specialâs unit â a unit areas. That system are manifestation of Asymmetric Desentralization principal system. Keywords: Free Trade Zone, Regional Authonomy, Asymmetric Desentralization System, Constitution.   Negara Kesatuan Republik Indonesia merupakan negara yang menganut sistem welfarestate dimana penyelenggaraan negara adalah bertujuan untuk mensejahterahkan masyarakat. Pelaksanaan kehidupan bernegara berdasarkan Ideologi Pancasila dan Konstitusi Undang-Undang Dasar Tahun 1945 dengan sistem pemerintahan menganut prinsip desentralisasi yang memberikan kewenangan pengelolaan dan pembangunan kepada Pemerintah Kota/Kabupaten kecuali seperti yang telah diatur dalam ketentuan peraturan perudangan. Pemberian kewenangan bagi Pemerintah Daerah ini merupakan perwujudan dari semangat pembangunan negara berdasarkan Otonomi Daerah. Dalam pemenuhan kesejahteraan masyarakat tersebut, pemerintah Negara Kesaatuan Republik Indonesia membentuk suatu kawasan yang diperuntukkan khusus bagi pengembangan dan strategi investasi dalam peningkatan pendapatan negara. Guna peningkatan tersebut, dibutuhkan otoritas pembangunan yang berfokus dalam pengembangan suatu kawasan di wilayah daerah yang khusus untuk menghadapi pembangunan infrastruktur dalam rangka pengembangan investasi. Hal ini membuat Pemerintah Pusat kembali melakukan intervensi kepada daerah untuk turut hadir langsung dalam melakukan pembangunan. Penerpan wilayah investasi tersebut adalah melalui Undang Undang Nomor 44 Tahun 2007 juncto Peraturan Pemerintah Nomor 46 Tahun 2007 tentang Perdagangan Bebas dan Pelabuhan Bebas Pulau Batam. Prinsip tersebut masih sejalan dengan amanah konstitusi terkait dengan pelaksanaan pemerintah daerah khususnya Pasal 18B ayat (1) yang menentukan bahwa negara menghormati satuan â satauan daerah yang bersifat khusus dan satuan â satuan daerah yang bersifat istimewa. Hal ini merupakan perwujudan dari konsep Desentralisasi Asimetris. Kata kunci: Wilayah Perdagangan Bebas, Otonomi Daerah, Desentralisasi Asimetris, Konstitusi